SOME ECONOMIC INDICATORS OF PRODUCTION OF COWS MILK IN THE REPUBLIC OF SERBIA - Radišić, Robert; Sredojevic, Zorica; Perišić, Predrag (Economics of Agriculture, 2021)
The subject of this research is cattle breeding with a focus on the production of cows milk in the Republic of Serbia. The main goal is to analyze the state and trends of cows milk production in Serbia during the last ten years in relation to production in Europe, the European Union and the world. Data from the SORS, FAO databases, etc. were used. In Serbia, 908,102 head of cattle are raised on 177,552 family farms, ie, an average of 5.11 head of cattle per farm. The number of cattle has dropped by more than 200,000 head over the last decade. In the total milk production in Serbia, cows milk accounts for 96.84%. The average milk yield of cows in Serbia is far below the European average. The highest average amount of milk is recorded in the Belgrade region, where 5,335 liters per milking head are produced in one year. The quality of cows milk in Serbia is far below EU standards, which is a key restriction on exports.